A review on application of blockchain in 5G and beyond networks: taxonomy, field-trials, challenges and opportunities - Tahir, Mohammad; Habaebi, Mohamed Hadi; Dabbagh, Mohammad; Mughees, Amna; Ahad, Abdul; Ahmed, Kazi Istiaque (Institute of Electrical and Electronics Engineers Inc., 2020)
Until now, every evolution of communication standard was driven by the need for providing high-speed connectivity to the end-user. However, 5G marks a radical shift from this focus as 5G and beyond networks are being designed to be future-proof by catering to diverse requirements of several use cases. These requirements include Ultra-Reliable Low Latency Communications, Massive Machine-Type Communications and Enhanced Mobile Broadband. To realize such features in 5G and beyond, there is a need to rethink how current cellular networks are deployed because designing new radio access technologies and utilizing the new spectrum are not enough. Several technologies, such as software-defined networking, network function virtualization, machine learning and cloud computing, are being integrated into the 5G networks to fulfil the need for diverse requirements. These technologies, however, give rise to several challenges associated with decentralization, transparency, interoperability, privacy and security. To address these issues, Blockchain has emerged as a potential solution due to its capabilities such as transparency, data encryption, auditability, immutability and distributed architecture. In this paper, we review the state-of-art application of Blockchain in 5G network and explore how it can facilitate enabling technologies of 5G and beyond to enable various services at the front-haul, edge and the core. Based on the review, we present a taxonomy of Blockchain application in 5G networks and discuss several issues that can be solved using Blockchain integration. We then present various field-trials and Proof of concept that are using Blockchain to address the challenges faced in the current 5G deployment. Finally, we discuss various challenges that need to be addressed to realize the full potential of Blockchain in beyond 5G networks. The survey presents a broad range of ideas related to Blockchain integration in 5G and beyond networks that address issues such as interoperability, security, mobility, resource allocation, resource sharing and management, energy efficiency and other desirable features.